Atlantic antagonism: Revolution and race in German-American Masonic relations, 1848–1861. Issue 3 (3rd July 2019) - Önnerfors, Andreas
ABSTRACT: After the 1848 revolutions in Europe, waves of European émigrés, many of them Germans, settled in the United States. These Forty-Eighters faced challenging choices in their relationship to American society, oscillating around assimilation, adaptation, alienation and open antagonism. The arrival of thousands of refugees from revolutions repositioned US politics within a transatlantic world, one increasingly shaped by multiple intersections and exchanges. Through the activities of German-speaking lodges in New York, this article analyses ideological tensions between Masonic universalism as espoused by émigrés and US Masonic practices, particularly with regard to racial biases. Persistent prejudices and significant differences in organizational culture led to escalating transatlantic Masonic tensions, pointing to deeper divergences in worldviews and self-perceptions. These tensions exposed the limits of the cosmopolitan ethos of Freemasonry when faced with the realities of cross-cultural negotiations between immigrant and US-born Freemasons.